Cadaveric analysis of transcranial versus endoscopic transorbital petrosectomy: comparison of surgical maneuverability and brainstem exposure - Kwon, Sae Min; Na, Min Kyun; Choi, Kyu-Sun; Byoun, Hyoung Soo; Nam, Yong Seok (Frontiers in Oncology, 2023)
Introduction: While accessing the posterior fossa, the anterior transpetrosal approach (ATPA) and endoscopic transorbital approach (ETOA) use the same bony landmarks during petrous apex drilling. However, owing to their contrasting surgical axes, they are expected to show differences in surgical view, maneuverability, and clinical implications. This study aimed to investigate the feasibility of ETOA in accessing the brainstem and to compare the surgical view and maneuverability of each approach. Methods: ATPA and ETOA were performed in four human cadaveric heads (eight sides and four sides in each procedure). The angle of attack (AOA) and surgical depth were measured at the target of interest (root exit zone [REZ] of cranial nerve [CN] V, VI, and VII). When measuring the area of exposure, the brainstem was divided into two areas (anterior and lateral brainstem) based on the longitudinal line crossing the entry zone of the trigeminal root, and the area of each was measured. Results: ATPA showed significantly greater value at the trigeminal REZ in both vertical (31.8±6.7° vs. 14.3±5.3°, p=0.006) and horizontal AOA (48.5±2.9° vs. 15.0±5.2°, p<0.001) than ETOA. The AOA at facial REZ was also greater in ATPA than ETOA (vertical, 27.5±3.9° vs. 8.3±3.3°, p<0.001; horizontal, 33.8±2.2° vs. 11.8±2.9°, p<0.001). ATPA presented significantly shorter surgical depth (CN V, 5.8±0.5 cm vs. 9.0±0.8, p<0.001; CN VII, 6.3±0.5 cm vs. 9.5±1.0, p=0.001) than ETOA. The mean area of brainstem exposure did not differ between the two approaches. However, ATPA showed significantly better exposure of anterior brainstem than ETOA (240.7±9.6 mm2 vs. 171.7±15.0 mm2, p<0.001), while ETOA demonstrated better lateral brainstem exposure (174.2±29.1 mm2 vs. 231.1±13.6 mm2, p=0.022). Conclusions: ETOA could be a valid surgical option, in selected cases, that provides a direct ventral route to the brainstem. Compared with ATPA, ETOA showed less surgical maneuverability, AOA and longer surgical depth; however, it presented comparable brainstem exposure and better exposure of the lateral brainstem.